THz generation from graphite - Ramakrishnan, G.; Chakkittakandy, R.; Planken, P.C.M. (2009 34th International Conference on Infrared, Millimeter, and Terahertz Waves, 2009)
Subpicosecond terahertz pulses are generated from the surfaces of graphite samples, when illuminated with femtosecond near-infrared laser pulses. Our experiments with highly oriented pyrolytic graphite samples suggest that the emission of THz radiation is caused by photoinduced transient charge carrier movements along the c-axis of the crystal. This is further confirmed by studying the effects of an in-plane magnetic-field which deflects the photocurrent and thereby changes the THz polarization. The experimental results point to two possible generation mechanisms, carrier acceleration in the space charge layer near the graphite surface and/or the photo-Dember effect.